2005
DOI: 10.1055/s-2005-872251
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid Catalysis: Organocatalytic Hydrogenation of Imines

Abstract: A new Brønsted acid catalysed hydrogenation of imines with Hantzsch dihydropyridine as the hydrogen source has been developed. Diphenyl phosphate (DPP) and various other acids catalyse this first metal-free hydrogen transfer to give various amines under mild reaction conditions. The development of catalysts for the asymmetric hydrogenation of imines is a topic of ongoing interest. Current methods include transition-metal-catalysed high-pressure hydrogenations, 1 hydro-silylations, 2 or transfer hydrogenations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
46
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(53 citation statements)
references
References 3 publications
2
46
0
5
Order By: Relevance
“…However, the yields were considerable lower as compared to other solvents. The best results with regard to both selectivity and reactivity were obtained in aromatic solvents ( Table 2, entries [3][4][5]. This tendency is in agreement with our earlier observations on Brønst-ed acid-catalyzed reactions where halogenated and aromatic solvents gave often superior selectivities.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…However, the yields were considerable lower as compared to other solvents. The best results with regard to both selectivity and reactivity were obtained in aromatic solvents ( Table 2, entries [3][4][5]. This tendency is in agreement with our earlier observations on Brønst-ed acid-catalyzed reactions where halogenated and aromatic solvents gave often superior selectivities.…”
supporting
confidence: 91%
“…In further experiments aiming to improve the enantioselectivities we decided to prepare different dihydropyridines 2a-e and tested them in our Brønsted acid-catalyzed reduction reaction (Table 4, entries [1][2][3][4][5]. Pleasingly, we found that the reaction proceeded with better enantiocontrol in all cases and the best selectivities of 8a (81% ee) were obtained if the allyl ester 2e was employed.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Figure 2b shows metal-free organocatalysts. These depend on strong imine activation by protonation, which allows use of weaker nucleophiles such as the Hantzsch ester [30][31][32][33] . Recently, strong Brønsted-acid activation and organometallic hydride catalysis have been combined 34,35 .…”
mentioning
confidence: 99%